The effectiveness of the e-learning system, the future gateway to develop the academic achievement in chemistry course for female students in the second secondary stage in Jeddah - Omeish, Safieh Muhammad Ali (Journal of Educational and Psychological Sciences, 2021)
This current research aimed at investigate the effectiveness of the e-learning system (the future portal) in developing the academic achievement of chemistry for second-grade secondary school students in Jeddah, and the research followed the experimental approach. The tool consisted in following an e-learning system using the electronic future gate system that was applied to an experimental group of (50) female students, against a control group of (50) students who studied using the traditional method. The study sample was randomly selected The results of the post-test showed that there are statistically significant differences at the level of significance (α≤0.05) between the experimental group and got a total mean (40.38 out of 50) and the control group and got a total mean (36.82 out of 50), and the difference is in favor of the experimental. This indicates that the method of teaching using e-learning (the gate of the future) has improved and promoted academic achievement in chemistry for second-grade secondary students in Jeddah., and the research came out with a set of recommendations, the most important of which is the need to adopt the use of the electronic learning system (the future gate) in teaching chemistry to students, due to its effectiveness and benefit in developing their academic achievement.